2022
DOI: 10.1002/cia2.12289
|View full text |Cite
|
Sign up to set email alerts
|

Two‐sided influence of dupilumab on alopecia areata co‐existing with severe atopic dermatitis: A case series and literature review

Abstract: Objectives: Alopecia areata (AA) often coexists with atopic dermatitis (AD). Recently, several reports suggested that dupilumab, an interleukin 4 receptor α-antagonist, administration could be a promising medication not only for severe AD but also for AA concomitant with AD (AD-AA). At the same time, dupilumab has also been reported to exacerbate AA in AD-AA cases. Thus, the efficacy of dupilumab on AA in AD-AA cases remains controversial. Methods:In this study, we retrospectively analyzed four AD-AA cases tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…One case of incontinentia pigmenti-associated scalp alopecia was reported. Clinical responses were mostly measured by the severity of alopecia tool (SALT) with a score < 10 defined as complete response ( Table 4 ) [ 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 ]. Noticeably, 13 pediatric patients were treated effectively with dupilumab [ 172 , 173 , 174 , 175 , 176 , 177 ].…”
Section: Resultsmentioning
confidence: 99%
“…One case of incontinentia pigmenti-associated scalp alopecia was reported. Clinical responses were mostly measured by the severity of alopecia tool (SALT) with a score < 10 defined as complete response ( Table 4 ) [ 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 ]. Noticeably, 13 pediatric patients were treated effectively with dupilumab [ 172 , 173 , 174 , 175 , 176 , 177 ].…”
Section: Resultsmentioning
confidence: 99%
“…3 Studies on dupilumab, another treatment option for AD cases complicated by AA, have shown conflicting results regarding its effects on AA. 4 We diagnosed this case of AA as a self-healing ADTA (sADTA) after nemolizumab administration. sADTA is defined as a rapidly progressive subtype of AA (RP-AA) that exhibits spontaneous recovery.…”
Section: A Case Of Atopic Dermatitis With Self-healing Acute Diffuse ...mentioning
confidence: 99%